Production performance and egg quality evaluation of indigenous chickens across different agro-ecologies of Southern Ethiopia - Bekele, Berhanu; Melesse, Aberra; Dessie, Tadelle; Bekele, B.; Melesse, A.; Esatu, Wondmeneh (Chiang Mai University, 2022)
Indigenous chickens were evaluated for their egg production, growth performances, and external and internal egg quality parameters across three agro-ecologies. For experiment 540 (180 male and 432 female) chickens were distributed to the three agro-ecologies (lowland, midland, and highland) at their 20 weeks age. Body weight was recorded from each chicken during distribution, 4th week, and 8th week after distribution into pre-selected households. Egg production potential was identified from the indigenous chickens across different agro-ecologies. Moreover, egg quality traits were evaluated from randomly selected 270 (90 from each agroecology) eggs. Egg production of indigenous chickens in the highland was 47.7 which was highly significantly (P = 0.0001) lower number than of midland (54.2) and lowland (51.4). Except for Shell weight, all the external egg quality parameters evaluated were exhibited significant differences across different agro-ecologies. Among the internal egg quality parameters only albumen weight had a significantly (P = 0.007) higher in midland than highland. Most of the variation in egg weight was due to the positive correlation with egg length (69%), and egg width (67%). There was a variation for performance and egg quality traits of indigenous chickens in different agro-ecologies, especially better in midland, which might be resulted from the variation in environment, feed resources availability, and better management followed by households.